In vitro evaluation of a novel immediate-release formulation of oxycodone (RoxyBond™) for the potential for abuse via injection - Kinzler, PhD, Eric R.; Pantaleon, BS, Carmela; Iverson, MPH, Matthew; Aigner, MD, Stefan (Journal of Opioid Management, 2020)
Objective: Immediate-release (IR) oxycodone formulations may be manipulated for nonoral routes of administration. Oxycodone abuse-resistant immediate-release (ARIR) is a novel abuse-deterrent formulation (ADF) of IR oxycodone. This study aimed to assess the intravenous (IV) abuse potential of Oxycodone ARIR relative to commercially available IR oxycodone tablets using in vitro laboratory studies. Design: Intact or manipulated tablets were incubated in 5 or 10 mL of room temperature water for increasing amounts of time. For each timepoint, syringeability, defined as the ability to draw up water-immersed intact or manipulated tablets into a syringe, was assessed on a scale of 1 (very easy) to 10 (impossible). If the prepared sample could be drawn into a syringe, the proportion of syringeable oxycodone was measured analytically. Results: In all conditions, it was nearly impossible to draw any liquid into a syringe from samples containing manipulated Oxycodone ARIR tablets (N = 5/ group), and most samples released very low concentrations (<10%) of their total oxycodone content, regardless of sample volume. In contrast, samples containing crushed IR oxycodone (N = 5/group) in small volumes of fluid were easily drawn into a syringe through the smallest needle, and more than 90% of the oxycodone content was released from relatively small sample volumes (5 mL). Conclusion: The difficulty required to prepare an injectable solution from Oxycodone ARIR when manipulated suggests that Oxycodone ARIR has abuse-deterrent properties that may deter IV abuse.